2016
DOI: 10.2174/1381612822666160127113912
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Functional Biomarkers in Schizophrenia with Neuroimaging

Abstract: Many of the most debilitating symptoms for psychiatric disorders such as schizophrenia remain poorly treated. As such, the development of novel treatments is urgently needed. Unfortunately, the costs associated with high failure rates for investigational compounds as they enter clinical trials has led to pharmaceutical companies downsizing or eliminating research programs needed to develop these drugs. One way of increasing the probability of success for investigational compounds is to incorporate alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The effects of pharmacologic manipulation on resting state connectivity in neuropsychiatric disease is a topic of recently increased interest, due in part to its potential applications in drug development (Smucny and Tregellas, 2013; Smucny et al, 2014b; Wylie et al, 2016). Comparatively few studies, however, have used task-associated connectivity in ascertain the neuronal effects of potential treatment interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of pharmacologic manipulation on resting state connectivity in neuropsychiatric disease is a topic of recently increased interest, due in part to its potential applications in drug development (Smucny and Tregellas, 2013; Smucny et al, 2014b; Wylie et al, 2016). Comparatively few studies, however, have used task-associated connectivity in ascertain the neuronal effects of potential treatment interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of more objective, intermediary biologic markers related to cognition, such as P50 sensory gating, can be helpful in this regard, as can the use of translational functional magnetic resonance imaging (fMRI) to refine animal models of cognition and determine optimally effective drug doses. 78,79 The success of this strategy will depend, however, on rigorous validation of these potential biomarkers. Lastly, as will be discussed below, in addition to clinical trials of nAChR agonists and PAMs, recent results have raised the hope that a nicotinic therapy may be able to impact adult cognitive dysfunction if administered early in development, even potentially in utero.…”
Section: Looking Forward: Continued Development Of Nicotinic Therapiesmentioning
confidence: 99%
“…Further, the improvements in symptoms with the combination treatments shown in Table 2 may be correlated with the prognostic and theranostic biomarkers (Perkovic et al, 2017; Weickert et al, 2013) shown in Figures 1–3. In other words, a Type 0 biomarker (a diagnostic marker) may be unlikely in psychiatry, and we may have to focus on Type I and II biomarkers (Biomarkers Definitions Working Group, 2001; Frank & Hargreaves, 2003; Terry & Callahan, 2020; Wylie, Smucny, Legget, & Tregellas, 2016). The Framingham Heart Study introduced the risk score calculator for coronary heart disease (Kannel, 2000).…”
Section: Biomarkersmentioning
confidence: 99%
“…One add-on medication enhancing MCCB composite score from 28-32 (baseline) to 50 or more (endpoint) is highly unlikely. Two add-ons are a feasible approach based on the effect sizes shown in Table 1 words, a Type 0 biomarker (a diagnostic marker) may be unlikely in psychiatry, and we may have to focus on Type I and II biomarkers (Biomarkers Definitions Working Group, 2001;Frank & Hargreaves, 2003;Terry & Callahan, 2020;Wylie, Smucny, Legget, & Tregellas, 2016). The Framingham Heart Study introduced the risk score calculator for coronary heart disease (Kannel, 2000).…”
Section: Biomarkersmentioning
confidence: 99%